The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1177/0267659111409276
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial protection during aortic surgery: comparison between Bretschneider-HTK and cold blood cardioplegia

Abstract: The ideal cardioplegic strategy in thoracic aorta operations requiring long cardiopulmonary bypass and cross-clamp time has not been established. Suboptimal myocardial protection may lead to myocardial damage and possible post-operative complications. We evaluate post-operative cardiac Troponin I (cTnI) release, low cardiac output syndrome (LCOS) and mortality, using a cold crystalloid single-dose intracellular or cold blood multidose cardioplegia in 112 elective or emergent thoracic aorta operation patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 24 publications
3
22
0
3
Order By: Relevance
“…Hypocalcemic solutions like Bretshcneider's HTK avoid these effects by inducing polarized arrest. This is also consistent with a previous study on patients undergoing open heart surgery for thoracic aorta (14). HTK and cold blood cardioplegic solutions-yet another hyperkalemic cardioplegic solution-assure similar myocardial protection in patients undergoing thoracic aorta operations.…”
Section: Discussionsupporting
confidence: 92%
“…Hypocalcemic solutions like Bretshcneider's HTK avoid these effects by inducing polarized arrest. This is also consistent with a previous study on patients undergoing open heart surgery for thoracic aorta (14). HTK and cold blood cardioplegic solutions-yet another hyperkalemic cardioplegic solution-assure similar myocardial protection in patients undergoing thoracic aorta operations.…”
Section: Discussionsupporting
confidence: 92%
“…Bretschneider (histidine-tryptophan-ketoglutarate, HTK) solution is frequently used for the induction of cardioplegic arrest in cardiac surgery (Careaga et al 2001). The high histidine concentration of 198 mM in Bretschneider solution was shown to buffer acidosis in the ischemic period (Scrascia et al 2011). This way, the prolonged existence of anaerobic glycolysis is favored, which would be otherwise inhibited by an acidic milieu.…”
Section: Introductionmentioning
confidence: 99%
“…14 For cases with cross-clamping time over 160 minute, HTK can provide a better myocardial protection when compared to CBC. 5 However, another study showed that there was significantly positive correlation between the cross-clamping times and the serum enzyme levels in the patients receiving HTK 3 ; the reason for these contradictory results is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Although more spontaneous ventricular fibrillation after aortic unclamping had been found in adult patients receiving HTK cardioplegia, one single dose of cold HTK gives equally good myocardial protection in cardiac surgery as multidose cold blood cardioplegia (CBC). [3][4][5] Experimental studies have shown, however, that HTK solution provides inadequate cardioprotection when compared to CBC. 6,7 The relative advantage of blood cardioplegia in relation to crystalloid cardioplegia is still the subject of debate in pediatric cardiac surgery.…”
mentioning
confidence: 99%